Donor Motivation In Donating Through Lazismu Sharia Crowdfunding A Qualitative Study On Digital Philanthropy Platforms With Thematic Analysis - Budiyono, Budiyono; Cahyono, Dwi; Maharani, Astrid (UNIVED Press, 2026)
The main objective of this study is to explore donor motivations in donating through the LAZISMU sharia crowdfunding platform, emphasizing experiences, personal considerations, and values ​​believed by donors. The research method used is thematic analysis, data collected through in-depth interviews with 13 LAZISMU donor participants. The results of the study indicate that religious, social, and personal motivations are the main factors for donors to donate through the LAZISMU sharia crowdfunding platform. Donors' experience of using a digital platform that is easy to donate not only strengthens religious beliefs but also provides a sense of security and comfort as well as strengthens loyalty and continuous donations. The influence of the social environment and trust in LAZISMU as a sharia institution provides additional motivation, as well as the main pillar of donor loyalty in donating online.